Influence of Interaction Between the Rates of Phosphorus Application and Temperature on Phosphorus Sorption-Desorption - Mahi, Y E L; Ibrahim, I S; Mohamed, A A; Elamin, E A (Annals of Arid Zone, 2016)
The effect of temperature was studied during sorption-desorption of graded quantities of phosphorus in two low-P semi-arid zone montmorillonitic clay soils from the Sudan: a Vertisol (Hosh series) and an Alfisol (Hagu series). During the equilibration times used, the results indicated that at low phosphorus application, sorption increased and desorption decreased with increase in temperature from 20 to 40Â°C. However, at high P application, sorption decreased and desorption increased with the same increase in temperature. At high P application, there seems to be present two discrete pools of sorbed P, a fast desorbable pool and a slow desorbable one, with desorption of the first being more sensitive to increase in temperature. A kinetic equation (Pd = a tb ) was found to describe the release of substantial amounts of P from both pools, where Pd is the amount of P desorbed at time t, and a and b are constants.